The frontiers of functionalized graphene-based nanocomposites as chemical sensors - Abdullah, Norli; Norizan, Mohd Nurazzi; Ngah Demon, Siti Zulaikha; Abdul Halim, Norhana; Mohd Azmi, Ahmad Farid; Victor Ernest, Victor Feizal Knight; Mohamad, Imran Syakir (De Gruyter Open Ltd., 2021)
Graphene is a single-atom-thick sheet of sp2 hybridized carbon atoms that are packed in a hexagonal honeycomb crystalline structure. This promising structure has endowed graphene with advantages in electrical, thermal, and mechanical properties such as room-temperature quantum Hall effect, long-range ballistic transport with around 10 times higher electron mobility than in Si and thermal conductivity in the order of 5,000 W/mK, and high electron mobility at room temperature (250,000 cm2/V s). Another promising characteristic of graphene is large surface area (2,630 m2/g) which has emerged so far with its utilization as novel electronic devices especially for ultrasensitive chemical sensor and reinforcement for the structural component applications. The application of graphene is challenged by concerns of synthesis techniques, and the modifications involved to improve the usability of graphene have attracted extensive attention. Therefore, in this review, the research progress conducted in the previous decades with graphene and its derivatives for chemical detection and the novelty in performance enhancement of the chemical sensor towards the specific gases and their mechanism have been reviewed. The challenges faced by the current graphene-based sensors along with some of the probable solutions and their future improvements are also being included.